Wetland birds in Turks and Caicos Islands I: A search for West Indian Whistling-ducks Dendrocygna arborea - Hilton, Geoff M; Cleeves, Tim; Murray, Tony; Hughes, Baz; Gibbs Williams, Ethlyn (Wildfowl, 2000)
The West Indian Whistling-duck (Dendrocygna arborea) is globally threatened due to significant population declines during the Twentieth Century. Turks and Caicos is a potentially important range-state for the species, but its status there has never been firmly established. A survey of West Indian Whistling-ducks was conducted in the Turks and Caicos Islands during February and March 1999 to make a preliminary assessment of the distribution and abundance of the species in the territory, and to test the viability of several different survey methods, including aerial surveys, tape-playback of the species' calls, and running transects through different habitat types. Only three-five West Indian Whistling-ducks were recorded at two sites on East Caicos suggesting the species may be genuinely scarce on the islands, overlooked, or seasonally absent. The possibility that West Indian Whistling-ducks behave as somewhat nomadic opportunists in response to unpredictable changes in wetland conditions is raised.